Pushing the boundaries – urban edge challenges in eThekwini Municipality. Issue 1 (2nd January 2016) - Sim, V.; Sutherland, C.; Scott, D.
Abstract : This paper explores the evolution of the urban edge concept in the eThekwini Municipality between 2002 and 2013. It uses the theory of governmentality to analyse the discourses and practices of the local state as it attempts to manage rapid urban growth and restructure the post-apartheid city. It reveals how and why the current concept, the urban development line (UDL), with its associated practices, has become a dominant discourse in city policy- and decision-making. It then examines the contestations that have emerged around the 'holding of the line' and it reflects on the level of participation and political engagement that has taken place in the construction of the UDL concept. The paper argues that if the UDL concept is to play a meaningful role in the sustainability of the city in the future, its value and 'politics' need to be debated by multiple actors including politicians, officials, the private sectors and civil society within and beyond the boundaries of the Municipality.